Origins and Leading Exponents of Secularism, in Its Educational Aspect, in Chile [Orígenes y Principales Exponentes del Laicismo, en Su Vertiente Educativa, en Chile] - Caiceo-Escudero, J (Associacao Sul Rio Grandense de Pesquisadores em Historia da Educacao, 2017)
The object of this article is to describe the emergence of secularism in Chile in the second half of the 19th century. Afterwards, it highlights the most outstanding figures in this line in the first half of the 20th century, especially for bringing the pedagogy of Dewey s educational into the development of the country, beating the French and German influences during the 19th century had lit up the secular and educational work; the above is, complemented by the present secular thought present in the National Education Awards of this field to be related with the pedagogy proposed by Dewey; they are important exponents of public education in the second half of the last century in the country. This process was carried out in the middle of discussions with representatives of sectors related to the Catholic Church.